DIAGNOSIS OF GROUPS OF ELECTRO-RADIO COMPONENTS ACCORDING TO THE TRANSIENT RESPONSES FOR THE DETECTION OF DEFECTS ON THE FUNCTIONAL CELLS - T. A. Ismailov; I. G. Mironenko; Kh. M. Gajiyev; T. A. Chelushkina (Вестник Дагестанского государственного технического университета: Технические науки)
Objectives. A method for diagnosing electronic components with minimally complicated control and measuring instrumentation and the ability to obtain information from internal control points of operating units is developed. Methods. The developed method for control of groups of electronic components presupposes the passage of a controllable influence through a few control points, connected via several electronic components. In addition, each electronic component contributes its share to the transformation of the parameter output, so the discrepancy of its allowable values for the identification of defective electronic component are required to assess the implication of the expected value of the probable defect of each electronic component in the schema with the aim of isolating it. The faulty component in the electronic circuit is identified by the minimum estimated variance, by which the magnitude of the defect will match the expected value of the electronic component parameter. Results. As a result of the control no more than ten groups of electrical components on functional cell matrices can be assessed as having a defective element by comparing the calculated variance values for each electrical component and the corresponding electrical component parameter itself. Conclusion. Diagnosing groups of electric components on transient characteristics for the detection of defects in the functional cell matrices enables efficiency control operations improvement and troubleshooting in the search for modern electronic equipment reliability.